The Accuracy of Analysts' Earnings Forecast in China M&A Market and The Role of the Stated Ownership in Forecast Accuracy - CAI, SITING (2017)
Analysis of earnings forecast accuracy is essential for all market participants including investors, managers, etc. (Bernard, 2008). It is considered that M&A transactions may lead to more complexities and difficulties in financial analysts’ forecasting activities, and in turns, result in greater forecast errors. Previous literature on empirical examinations of forecast accuracy has provided evidence that the increased forecast errors exist in the M&A activities in different countries (Haw et al., 1994; How et al., 2005; Coen et al., 2007). This study aims to provide some evidence on financial analysts’ forecast accuracy in China M&A market, and by using the sufficient evidence on Chinese state-owned enterprises (SOE), to explore the role of the stated ownership in financial analysts’ forecast accuracy.